Ethnomathematics in Religious Tourism Architecture: Mathematical Concepts and Islamic Geometric Ornaments at Alun-Alun Cililin - Ratna Marlina; Wahyu Hidayat; Tatang Supriatna (Universitas Papua, 2026)
Meaningful learning is a key objective of the contemporary Indonesian curriculum, emphasizing conceptual understanding rather than the mere memorization of mathematical formulas. However, the integration of cultural and spiritual dimensions into mathematics instruction remains limited. Ethnomathematics offers a valuable approach to addressing this gap by exploring mathematical ideas embedded in cultural artifacts. This study investigates the philosophical meanings reflected in the Islamic geometric patterns of Alun-Alun Cililin Park, West Bandung Regency, Indonesia, and examines their relationship with mathematical concepts. An exploratory qualitative design with a semiotic approach was employed. Data were collected through observation and documentation and analyzed using Charles Sanders Peirce’s semiotic framework, consisting of representamen, object, and interpretant. The analysis identified various mathematical concepts embedded in the geometric patterns, including plane geometry (quadrilaterals, pentagons, and circles), solid geometry (rectangular prisms, trapezoidal prisms, cylinders, and truncated cones), and transformational geometry (rotation, dilation, and reflection). The patterns also embody philosophical values related to mutual cooperation, cultural preservation, social solidarity, spiritual preparedness, and the pursuit of a meaningful life. These findings highlight the potential of Islamic geometric patterns as culturally grounded resources for connecting mathematical learning with cultural and spiritual values, thereby contributing to the development of more meaningful and contextually relevant mathematics education.